Influence of Project Management Functions on Effective Implementation of Donor Funded Projects in Kenya - Kamba, Mwangangi Stephen; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Projects remain the instruments of choice for policy makers in international development. Yet, paradoxically, the poor implementation of projects and the disappointment of project stakeholders and beneficiaries seem to have become the rule and not the exception in contemporary reality. Kenya is one of the countries that receive a lot of donor support to set up projects for the purpose of improving the status of its population such as employment, alleviation of poverty, increase of economic performance and supporting social cohesion. Despite enormous resources channeled by donors in setting up these projects, little impact has been realized as trends in implementation rates continues to surge as a result of lack of Project Management Functions. The main purpose of this study was to establish influence of Project Management Functions on effective implementation of donor funded projects in Kenya. The study was guided by the following specific objectives: To find out the influence of planning and organizing on effective implementation of donor funded projects in Kenya; To investigate the influence of monitoring and evaluation on effective implementation of donor funded projects in Kenya; To examine the influence of directing and controlling on effective implementation of donor funded projects in Kenya; To study the influence of directing and controlling on effective implementation of donor funded projects in Kenya and to establish the influence of coordination on effective implementation of donor funded projects in Kenya. The study was built on the contingency theory, theory of constraints, theory of agency and theory of change. The target population of this study was 177 that is project managers (top and middle level), chairpersons of the beneficiary groups and representatives of the donor agencies in Mutitu Sub-County. Donor agencies and targeted beneficiaries from each sampled donor funded projects. The primary data was gathered from the questionnaires